2019
DOI: 10.1002/bmc.4580
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and bioavailability study of ginsenoside Rk1 in rat by liquid chromatography/electrospray ionization tandem mass spectrometry

Abstract: Ginsenoside Rk1 (Rk1) exhibited various potent biological activities. However, its pharmacokinetic profile in vivo remains unclear. In the present study, a simple and sensitive liquid chromatography tandem mass spectrometry method was developed and validated for determination of Rk1 in rat plasma and applied in a pharmacokinetic study. The sample was precipitated with acetonitrile and separated on a Zorbax Eclipse XDB C18 column (50 × 2.1 mm, 1.8 μm). The mobile phase was composed of 0.1% formic acid in water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…The typical equations were y = 0.00891059x + 0.00183307 (R 2 > 0.995) and y = 0.00882761x + 0.00183307 (R 2 > 0.991) for ginsenosides Rk1 and Rg5, respectively, where y and x are peak area ratios and concentration ratios of analytes to IS. The LLOQs of ginsenosides Rk1 and Rg5 were 2 ng/ml (S/N >10), which was lower than previously established method with the LLOQ of 5 ng/ml for ginsenoside Rk1 (Li, Li, Zhang, Fan, & Liu, 2019).…”
Section: Linearity and The Lowest Limit Of Quantificationcontrasting
confidence: 60%
See 1 more Smart Citation
“…The typical equations were y = 0.00891059x + 0.00183307 (R 2 > 0.995) and y = 0.00882761x + 0.00183307 (R 2 > 0.991) for ginsenosides Rk1 and Rg5, respectively, where y and x are peak area ratios and concentration ratios of analytes to IS. The LLOQs of ginsenosides Rk1 and Rg5 were 2 ng/ml (S/N >10), which was lower than previously established method with the LLOQ of 5 ng/ml for ginsenoside Rk1 (Li, Li, Zhang, Fan, & Liu, 2019).…”
Section: Linearity and The Lowest Limit Of Quantificationcontrasting
confidence: 60%
“…Compared with the extensive literature on the pharmacological activities, few works have been done on the pharmacokinetics, which is crucial for drug discovery and development (Jones et al, 2015). Although a pharmacokinetic study of ginsenoside Rk1 has been done (Li, Li, Zhang, Fan, & Liu, 2019), pharmacokinetic information on ginsenoside Rg5 is absent. In addition, pharmacokinetic studies of ginsenosides Rk1 and Rg5 could be helpful to clarify the relationship between pharmacokinetics and the structural preference of ginsenosides.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the bioavailability of major ginsenosides is very low. The minor ginsenosides such as G-Rk1 and G-Rg5, which are transformed from the major ginsenosides through a deglycosylation, have higher bioavailability and absorption [ 41 ]. In this study, we confirmed the anti-tumor effect of G-Rk1 and G-Rg5 on highly metastatic liver cancer cell line, MHCC-97H.…”
Section: Discussionmentioning
confidence: 99%
“…9 As a transformation metabolite of gut microbiota, Gin Rg3 is found to be easily absorbable, which is different from other ginsenosides such as Rd and Rk. 10 However, we still know little about the immunomodulatory effect of Gin Rg3, a key metabolite in the UC model. Therefore, it is necessary to clarify the role and mechanism of Gin Rg3 in UC as soon as possible to explore the pharmacological effects of ginseng in UC.…”
Section: ■ Introductionmentioning
confidence: 99%